Penghambatan Respirasi Djaringan oleh Ekstrak Daun Sambiloto, Andrographis paniculata Nees - P. Soedigdo; An An Kurniasari; Thung Loan Kiao; Soekeni Soedigdo (Journal of Mathematical and Fundamental Sciences, 1972)
It was shown recently that crude extracts prepared from the leaves of Andrographis paniculata Nees have a significant hypoglycaemic effect when given orally to rabbits as well as to normal and diabetic persons (2). In the course of further investigations, the effect of the extract on cell respiration was studied. Bovine heart muscle homogenates were used for the experiments. Oxygen uptake was followed in a Warburg apparatus at 30°C with air as the gas phase. In the absence of added substrate the homogenate showed a considerable oxygen uptake, most probably due to the oxidation of endogenous substrates. It appeared that this oxygen consumption was inhibited by the crude extract added at various concentrations. Whether this effect was caused by the hypoglycaemic substance is still unanswered. Work is in progress to isolate the physiologically active compounds.